1999
DOI: 10.1002/(sici)1099-0992(199911)29:7<961::aid-ejsp977>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

When stereotype-based expectancies impair performance: the effect of prejudice, race, and target quality on judgments and perceiver performance

Abstract: High-and low-prejudiced participants were presented with a lecture segment in which the race of the professor (White or Black) and lecture quality (high or low) were manipulated. Consistent with predictions, low-prejudiced participants were more extreme in their evaluations (more negative) and performed more poorly on test items when presented with an expectancy-violating low-quality Black lecturer. Highprejudiced participants were more extreme in their evaluations (more positive) and performed more poorly whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Shifting standards also come into play in the communication and subsequent translation of stereotype‐relevant characteristics (Biernat & Eidelman, ; Biernat, Tocci, & Williams, ; Collins, Biernat, & Eidelman, ). For example, the subjective evaluation of a “pretty good” student gets translated into a lower objective performance (i.e., lower GPA) when the student is Black versus when the student is White or when the race of the student was unknown (Collins et al., ) and these stereotype‐based expectancies have influence on performance (Vescio & Biernat, ). Given the social significance of social class, these translation effects have implications for social interactions.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Shifting standards also come into play in the communication and subsequent translation of stereotype‐relevant characteristics (Biernat & Eidelman, ; Biernat, Tocci, & Williams, ; Collins, Biernat, & Eidelman, ). For example, the subjective evaluation of a “pretty good” student gets translated into a lower objective performance (i.e., lower GPA) when the student is Black versus when the student is White or when the race of the student was unknown (Collins et al., ) and these stereotype‐based expectancies have influence on performance (Vescio & Biernat, ). Given the social significance of social class, these translation effects have implications for social interactions.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…Cultural stereotypes contain information about a group's relative social status and explanations for that status (Eagly & Karau, 2002;Wittenbrink, Gist, & Hilton, 1997;Vescio & Biernat, 1999). Because stereotypes explain social reality, they are relevant to a wide array of achievement domains.…”
Section: When Do Powerful People Behave In Patronizing Waysmentioning
confidence: 99%
“…Women are compared with one's general expectations for women, and men are compared with one's expectations for men. In a masculine domain, a woman who exhibits basic counterstereotypic competencies (e.g., agency, athleticism) may surpass low stereotype-based expectations, and powerful people's judgments of and behavior toward her become more extreme in the direction of the expectancy violation (e.g., Jussim, Coleman, & Lerch, 1987; Vescio & Biernat, 1999). As a result, women who are surprisingly competent receive more praise and pats on the back than similarly competent but non-expectancy-violating men.…”
Section: What Is Patronizing Behavior?mentioning
confidence: 99%
See 1 more Smart Citation
“…The Modern Racism Scale is one of the most commonly used measures of bias toward African Americans. Scores on the Modern Racism Scale are positively correlated with other subtle measures of bias toward African Americans (Saucier & Miller, 2003), negatively correlated to motivation to be non-prejudiced (Lowery et al, 2001;Plant & Devine, 1998), and has been used to predict divergent reactions to African Americans and Whites (Vescio & Biernat, 1999). The test-retest correlations for the scale were reported by the authors to be .93 (McConahay et al, 1981), and other studies have found test-retest correlations ranging from .76 to .86 (Cunningham et al, 2001).…”
Section: Methodsmentioning
confidence: 95%